Strategi Pengembangan Sumber Daya Manusia Tenaga Pendidik dan Kependidikan dalam Menghadapi Pembelajaran Abad ke-21 - Wiwin Sunarni; Ibrahim, Rustam (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The paradigm shift in education during the Fourth Industrial Revolution demands that educators and education personnel possess competencies aligned with 21st-century learning. Human resource development (HRD) is a key strategy to improve the quality of education that is responsive to technological advances and the demands of the digital era. This study aims to analyze HRD strategies for educators and education staff in addressing the challenges of 21st-century learning. A qualitative approach with a descriptive design was employed. Data were collected through observations, in-depth interviews, and documentation. Thematic analysis was used, involving data reduction, presentation, and reflective conclusion drawing. The findings reveal that HRD strategies include in-house training programs, involvement in Teacher Working Groups (KKG), continuous coaching, and comparative studies with other institutions. These strategies enhance technological competence, creativity, and collaboration among educators. However, challenges remain, particularly in the form of digital skill gaps and limited infrastructure that hinder the optimal implementation of development programs. The implication of this study emphasizes the importance of structured, sustainable, and collaboratively supported HRD in shaping educators who are adaptive to 21st-century learning